Ativação do peróxido de hidrogênio para a epoxidação de olefinas não-funcionalizadas - Holleben, Maria Luiza Ambros von (1997)
A general overview about the more useful activating agents of the hydrogen peroxide in the epoxidation of unfunctionalized alkenes, focusing mechanistic proposals. Moreover, reactivity and stereochemistry, including the stereogenic effect of the hydroxyl group is presented.